Die gesag waarmee Jesus geleer het volgens Matteus 7:29 - Viljoen, Francois P. (HTS teologiese studies, 2012)
The authority with which Jesus taught according to Matthew 7:29. This article focuses on Matthew’s claim as conclusion to the Sermon to the Mount that Jesus preached with unparalleled authority. To grasp the meaning and intention of this claim in Matthew 7:29, this statement is read as part of the development of the theme of Jesus’ authority within the Matthean gospel. The authority of Jesus is interpreted in relation with the authority of powerful imperial and Jewish figures of his time and the development of the concept of ἐξουσία [authority] in the first gospel. It is argued that by this claim Matthew intends to confirm the conviction of his community that Jesus is the Messiah and authoritative interpreter of the Law. Matthew argues that God’s kingdom has come despite opposition from the synagogue and its leaders, and of the physical dominance of imperial powers. As the church enjoys a privileged position in this kingdom, it has credibility and the authority to execute the commandments of Jesus.